Cerebral oedema in enuretic children during low-dose desmopressin treatment: a preventable complication - Lebl, J; Kolská, M; Zavacká, A; Eliásek, J; Gut, J; Biolek, J (European journal of pediatrics, 2001)
Seven cases of cerebral oedema have been observed in enuretic children during low-dose desmopressin (DDAVP) treatment given in a dose of 7-21 microg daily in the Czech Republic between 1995 and 1999, after the drug started to be marketed for this indication and delivered in simple bottles with a dropper. All seven children (age 5-11 years, four boys) experienced a period of unconsciousness but all recovered without sequelae. In most cases, safety measures were underestimated and natraemia was not regularly controlled. Two children developed cerebral oedema after excessive water intake in preparation for uroflowmetry, another one drank much during a hot summer day, in one diabetes insipidus was not recognised and two children were clearly non-compliant with reduced fluid intake on a long-term basis. Only in one child, no risk factor was found. Conclusion. Proper selection and instruction of patients is needed to avert cerebral oedema during treatment with desmopressin for nocturnal enuresis.
Keywords: dítě; Water Intoxication; Enuresis; Brain Edema; ledvinné látky; desmopresin; předškolní dítě; lidé; enuréza; Deamino Arginine Vasopressin; Hyponatremia; intoxikace vodou; Consumer Product Safety; Female; edém mozku; Male; ženské pohlaví; hyponatremie; Child; Humans; mužské pohlaví; Renal Agents; Child, Preschool; spotřebitelská bezpečnost produktů